THE INFLUENCE OF SERVICE QUALITY ON PURCHASING DECISIONS AT RICHEESE FACTORY IN LHOKSEUMAWE CITY - Putri Rahmadhini; Nursakinah Ritonga; Sufi; Nursanjaya; Lisa Iryani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Service quality is a dynamic condition that is closely related to products, services, human resources, as well as processes and the environment that can at least meet or even exceed the expected service quality. Service quality is one measure of success in providing a guarantee of satisfaction for consumers, if consumers are satisfied with a service, they will become loyal and devoted consumers to the company that provides the service. This study aims to determine the effect of Service Quality on Purchasing decisions at Richeese Factory Lhokseumawe City. This study uses a quantitative approach which aims to determine whether Service Quality has a Positive and Significant influence on Purchasing Decisions. The population in this study were all consumers who had bought at Richeese Factory Lhokseumawe City which was not known with certainty and the determination of the sample using the "purposive sampling" method and the formula used in determining the number of respondents using the Lemeshow formula so that the number of respondents was 96 respondents. In proving and analyzing this, validity and reliability tests, classical assumption tests, simple linear regression tests and t tests (partial) are used. This result is proven by the T test that the service quality variable has a positive and significant effect on purchasing decisions with a value of????ℎ????????????????????>????????????????????????, which is 13.863> 1.986 and a significance value of 0.000 <0.05 so that H0 is rejected and Ha is accepted. The better the service quality, the more consumer purchasing decisions will increase for Richeese Factory products.